2021
DOI: 10.3892/etm.2021.10598
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy positively regulates Wnt signaling in mice with diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is a microvascular complication of diabetes. Aberrant Wnt signaling activation plays a pathological role in DR. However, the underlying mechanisms of aberrant Wnt signaling in DR remain unknown. Autophagy has been reported to be involved in the pathophysiology of DR. The present study aimed therefore to investigate the regulatory effects of autophagy on Wnt signaling in DR. Wnt signaling was activated in the retina of db/db mice combined with an increase in the expression of the autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Therefore, more new targets for the treatment of DR need to be sought. An increasing number of studies have shown that autophagy and ferroptosis are involved in the progression of DR (Tang et al 2022 ; Ye et al 2021 ). Therefore, this study further investigated how autophagy and ferroptosis play a role in DR, which may provide a potential avenue for the treatment of DR.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more new targets for the treatment of DR need to be sought. An increasing number of studies have shown that autophagy and ferroptosis are involved in the progression of DR (Tang et al 2022 ; Ye et al 2021 ). Therefore, this study further investigated how autophagy and ferroptosis play a role in DR, which may provide a potential avenue for the treatment of DR.…”
Section: Discussionmentioning
confidence: 99%
“…However, considerable evidence suggests RAPA had adverse effects like diabetes-like symptoms, gastrointestinal disorders, and increased infection risk. Exploring alternatives with fewer side effects was important [12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to apoptosis, some studies have found that impaired autophagy also occurs in RMCs under high glucose conditions. Autophagy plays important roles in biological functions and cell survival [12][13][14][15][16][17]. Dysfunction of autophagy ux is correlated with ageing-related diseases like neurodegeneration and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Wnt3a, a Wnt ligand, can regulate the activity of AMPK and thus autophagy status inside the target cells ( Ríos et al, 2018 ). In an experiment, Ye and co-workers indicated that diabetic retinopathy is associated with a close interaction between autophagy and the Wnt signaling pathway ( Ye et al, 2021 ). They found that the inhibition of autophagy response led to the downregulation of the Wnt signaling pathway and thus an impaired angiogenesis activity.…”
Section: Role Of Autophagy In Pericyte Activitymentioning
confidence: 99%
“…In diabetic db/db mice, the physiological activity of autophagy can alleviate the detrimental effects of metabolic abnormalities of course when the relevant molecular machine works properly. Despite the stimulation of Frontiers in Cell and Developmental Biology frontiersin.org BCLN1 and LC3 in vascular cells and retinal cells after being exposed to prolonged diabetic conditions, P62 activity is downregulated, leading to an incomplete autophagic response and the accumulation of exhaust materials inside the cells (Ye et al, 2021). That said, the accumulation of P62 at later autophagic steps not only promotes cell injury but also can abolish functional behavior of progenitor cells and even differentiation toward vascular cells (Rezabakhsh et al, 2017).…”
Section: Diabetic Conditionsmentioning
confidence: 99%